Bidirectional dc to dc Converters: An Overview of Various Topologies, Switching Schemes and Control Techniques - Ravi, Deepak; Mallikarjuna Reddy, Bandi; S.L, Shimi; Samuel, Paulson (International Journal of Engineering and Technology, 2018)
Bidirectional dc to dc converter is used as a key device for interfacing the storage devices between source and load in renewable energy system for continuous flow of power because the output of the renewable energy system fluctuates due to change in weather conditions. In electric vehicles also, bidirectional converter is used between energy source and motor for power supply from battery to motor. Thus, bidirectional dc to dc converters are getting more and more attention in academic research and in industrial applications. Bidirectional dc to dc converters work in both buck and boost mode and can manage the flow of power in both the direction between two dc sources and load by using specific switching scheme and phase shifted control strategy and hence generated excess energy can be stored in batteries/super capacitors. Therefore, the basic knowledge and classification of bidirectional dc to dc converters on the basis of galvanic isolation, the comparison between their voltage conversion ratio and output current ripple along with various topologies researched in recent years are presented in this paper. Finally, zero current and zero voltage soft switching schemes and phase shifted controlling techniques are also highlighted.Â Â Â